Analysis of the association between non-alcoholic fatty liver disease and mortality in United States adults - Rong, Fen; Mai, Yiyi; Shou, Lujia; Zhu, Xinya; Li, Meiyue; Zhu, Liuchen; Sun, Xiuli; Zhao, Xinhua (Frontiers in Nutrition, 2024)
Background: Non-alcoholic Fatty Liver Disease (NAFLD) is a prevalent condition characterized by the accumulation of fat in the liver, often linked with increased risk for multi-systemic diseases. This study aims to investigate the relationship between NAFLD and mortality, particularly all-cause and cardiovascular mortality, among US adults. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) were utilized, encompassing 80,312 participants from 2003-2004 to 2017-2018. After exclusions for incomplete data, potential other liver diseases, and significant alcohol consumption, the final analytical cohort included 32,698 participants. The Fatty Liver Index (FLI), a non-invasive diagnostic tool, was used to identify NAFLD. Covariates included demographic characteristics, lifestyle factors, and biochemical parameters. Survival analysis was conducted using a weighted Cox proportional hazards regression model to quantify the impact of NAFLD on mortality. Results: The study revealed that NAFLD was significantly associated with increased risks of all-cause and cardiovascular disease (CVD) mortality. The hazard ratios (HRs) from the survival analysis consistently indicated a higher risk among participants with NAFLD compared to those without. Subgroup analyses further confirmed the association, with notable exceptions in certain subgroups such as those with high school education and diabetes. Additionally, a nonlinear relationship between serum uric acid (SUA) levels and mortality risk was identified among NAFLD participants. Conclusion: NAFLD is a significant risk factor for all-cause and CVD mortality in US adults. The findings underscore the importance of early detection and intervention for NAFLD to mitigate its impact on public health. Further research is needed to explore the complex interactions between NAFLD, SUA levels, and mortality, particularly in high-risk subgroups.